Daring adventures in paint : find your flow, trust your path, and discover your authentic voice techniques for painting, sketching and mixed media - McDonough, Mati Rose (Beverly, Mass. Quarry Books, 2012)
"Daring adventures in paint is a colorful, whimsical adventure of a book that explores inspirational paint and mixed-media techniques. Written by the well-loved artist/illustrator/blogger Mati Rose McDonough, this book's approach to making art is a bit like uncovering a hidden treasure, a treasure that resides within each aspiring artist. Through a myriad of both practical applications and creative exercises, Mati shows artists how to 'find their magic'--the place of confidence from which they can access the vision of what they want to share with the world"--Provided by publisher.
Keywords: Collage; Mixed media painting; Crafts & Hobbies -- Mixed Media; Crafts & Hobbies -- Painting